Peaks And Valleys - "Johnson, Spencer." (New York)
Before the story -- Feeling low in a valley -- Finding answers -- Forgetting -- Resting -- Learning -- Discovering -- Sharing -- Using peaks and valleys -- A summary -- Enjoying a peak -- After the story.
Keywords: SUCCESS IN BUSINESS.;SUCCESS.